Development of clinical competence assessment tool for novice physical and occupational therapists-a mixed Delphi study - Kanada, Yoshikiyo; Sakurai, Hiroaki; Sugiura, Yoshito; Hirano, Yudai; Koyama, Soichiro; Tanabe, Shigeo (Journal of physical therapy science, 2016)
[Purpose] The aim of this study was to clarify essential abilities of novice physical and occupational therapists for independent execution of their duties and to develop a clinical competence assessment tool. [Subjects] Forty-five experienced therapists participated in this study. [Methods] A two-phase mixed-methods design was used. First, semi structured interviews were conducted on 15 experienced therapists to create a comprehensive list of essential abilities that novice therapists need. Second, 30 experienced therapists participated in a two-round Delphi study to select items for the assessment tool being developed. [Results] Fifty-five items were extracted and classified into three categories: basic attitudes, therapeutic skills, and clinical practice-related thoughts. [Conclusion] Present results suggest that not only knowledge of execution of therapy-related duties and therapeutic skills is essential in novice therapist, but also appropriate abilities in social adjustment, self-management, and self-education. The newly developed tool might be useful for postgraduate education in clinical practice.